Central banking : theory and practice in sustaining monetary and financial stability - Moenjak, Thammarak (Wiley, 2014)
Understand the theories and interpret the actions of modern central banks Central Banking takes a comprehensive look at the topic of central banking, and provides readers with an understanding and insights into the roles and functions of modern central banks in advanced as well as emerging economies, theories behind their thinking, and actual operations practices. The book takes a systematic approach to the topic, while providing an accessible format and style that is appropriate for general audiences and students with only a minimal macroeconomic background. Theoretical reviews and examples.